Whale talk - Crutcher, Chris (Greenwillow Books, 2001)
Intellectually and athletically gifted, TJ, a multiracial, adopted teenager, shuns organized sports and the gung-ho athletes at his high school until he agrees to form a swimming team and recruits some of the school's less popular students.